Normothermic machine perfused organs as models of drug pharmacokinetics and therapeutic delivery - Clark, TL (2022)
Less than 10% of drug candidates successfully pass through clinical trials and gain regulatory approval. One of the causes of translational failure is poor drug pharmacokinetics which are inadequately predicted by preclinical studies. Despite improvements in pharmacokinetic prediction in recent years, the circulating kinetics of many novel biologic agents, nanomedicines and drug delivery systems which exhibit transporter-mediated clearance, and size-dependent uptake by the reticuloendothelial system (RES), do not scale between species in a predictable manner and suffer with inadequate delivery to the therapeutic target. This hinders clinical translation, thus highlighting the need for more accurate preclinical testing to predict human drug disposition and facilitate improved drug delivery.